STUDIES IN LEGUMINOSAE 15. NEW TAXA OF DALBERGIA LINN. F. FROM INDIA AND BURMA - Thothathri, K. (Research Center for Biology, 1972)
During a study of the Indo-Burmese species of the genus Dalbergia Linn. f. the author came across an interesting specimen from Travancore, wrongly identified as D. congesta Grah. ex Wt. & Arn. This specimen differs markedly from the. latter in the conspicuous, persistent bracteoles which remain even after fruiting.